2018
DOI: 10.1097/md.0000000000009741
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the incidence of in-hospital cardiopulmonary resuscitation on Monday–Wednesday and Thursday–Sunday

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As reported previously 21 , the average number of ICPR performed for IHCA cases per 1000 patients per month was 4.22 (SD: 1.13) from 2007 to 2016. The initial ROSC rate following ICPR from IHCA was reported to be 72.3% from 2012 to 2016 22 . A rapid response system has been in place since 2013 to reduce the incidence of IHCA at SNUBH 23 , and ICPR has been performed for IHCA by both the rapid response system and an on-duty resident team 24 .…”
Section: Methodsmentioning
confidence: 99%
“…As reported previously 21 , the average number of ICPR performed for IHCA cases per 1000 patients per month was 4.22 (SD: 1.13) from 2007 to 2016. The initial ROSC rate following ICPR from IHCA was reported to be 72.3% from 2012 to 2016 22 . A rapid response system has been in place since 2013 to reduce the incidence of IHCA at SNUBH 23 , and ICPR has been performed for IHCA by both the rapid response system and an on-duty resident team 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, reduced hospital staffing on the weekend and the effect of this factor on hospital care were reported to be associated with increased mortality in hospitalized patients 23,24 . In a recent cohort study conducted at a single tertiary academic hospital in South Korea, the incidence of in‐hospital cardiopulmonary arrest was higher during Thursday–Sunday than during Monday–Wednesday, 25 suggesting that the reduced hospital staff during the weekend or later in the week might have a negative effect on the outcomes of hospitalized patients. Postoperative complications, including fatal events, occur commonly after cardiac surgery, 26 and the staffing of experienced intensivists during nighttime or weekend shifts was shown to improve patient outcomes after postoperative cardiac surgery 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The "weekend effect" on ICPR implies that the patients who undergo ICPR on the weekend would be associated with worse clinical outcomes after ICPR compared to those who undergo ICPR on weekdays (3)(4)(5)(6). We previously analyzed 1195 in-hospital CPR cases and studied CPRs by day of the week, and observed that the occurrence of intra-hospital CPRs varied by Mondays-Wednesdays and Thursdays-Sundays, and that the return of spontaneous circulation (ROSC) rate of ICPRs occurring on Sundays was low even after correction (3). In a study using data from a multicenter or regional ICPR registry, patients who received ICPR on weekends/nights were associated with lower survival to discharge (5,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%